Two-Year College Students Report Multiple Benefits From Participation in an Integrated Geoscience Research, Coursework, and Outreach Internship Program. (October 2021) - Stofer, Kathryn A.; Chandler, Jhenai W.; Insalaco, Stephanie; Matyas, Corene; Lannon, Heidi J.; Judge, Jasmeet; Lanman, Brandan; Hom, Bobby; Norton, Heather
Objective: Despite the availability of high-paying, high-demand careers, few women and students from underrepresented racial and ethnic minorities enter undergraduate programs understanding what the geosciences are and associated available career opportunities. This problem is compounded for students from backgrounds underrepresented in the United States. High-impact practices, such as mentoring, internships, undergraduate research experiences, and cohort-building, increase recruitment and retention of underrepresented students in science, technology, engineering, and math at 4-year institutions. What is not yet clear is the impact these interventions have on underrepresented students at two-year colleges, where the STEM pathway has become a main postsecondary school entry point for these students due to the affordability, flexibility, and academic support provided. Therefore, we designed, implemented, and researched a year-long program providing underrepresented students at a two-year college exposure to several of these experiences.Methods: We interviewed program participants about their perceptions and experiences in the program. Analysis proceeded using constant comparison.Results: Participants reported benefits from networking opportunities, gains in confidence, and gains in job skills, while some reported challenges for participation such as communication and time expectation conflicts; participants also struggled to balance the program with employment needs on top of school requirements. Different aspects of the program benefited different students, suggesting that all of these experiences could support recruitment and foster interest in geoscience for underrepresented students at two-year colleges.Conclusion: We conclude with implications for future research, program enhancements, and time constraint and mentoring needs related to characteristics of two-year college students.